Comparative evaluation of mechanical properties, scanning electron microscopy (SEM) analysis, and water holding capacity of recycled and virgin high-density polyethylene (HDPE) plastics: a study on the morphological and physical characteristics of thermoplastic materials - Okon Wilson, Emmanuel; Amgbari, Charles Onyinegbaliwene (Mechanical Technology and Engineering Insights, 2024)
Municipal solid waste management when poorly done serves as a breeding ground for pathogens which cause loss of arable land and diseases directly or indirectly. In a bid to combat the geometrical increase in waste conditioned by the subsequent increase in human population, recycling has become a solution. One major throwback to recycling is the belief that due to the thermal decomposition of plastic, the recycled product would have different properties from that of the original plastic product hence rendering its suitability for use in production invalid. This research evaluated the recycling process of High Density Polyethylene (HDPE) plastic and carried out mechanical property characterization tests which included tensile test, hardness test and impact test on the recycled HDPE product. 200g of HDPE plastic was used as specimen melted in a furnace and poured into a wooden mold to cool. The cooled material was subjected to tensile, impact and hardness tests. The test exposed that the Rockwell Hardness Number (RHN) for the examined HDPE material was given as 50.0mm. The tensile test was evaluated to be 25.60MPa. The sample had an impact test value of 284J/m2. It was also determined that the sample had a yield strength of 21.412MPa. The mechanical properties of hardness number, tensile strength, impact strength and yield stress of an original un-recycled HDPE plastic material are given respectively as (60.0-70.0mm), (21.4–30.3)MPa, (158–505 J/m2) and (17.9–31.0)MPa respectively. The water absorption test revealed that the % absorption from the virgin and recycled HDPE plastics were 0.015% and 0.027% respectively. The high value of the recycled HDPE owing to the presence of additives and impurities. Comparison of these properties between un-recycled (virgin) and recycled HDPE plastic show that the values gotten are within the acceptable range and hence, recycled HDPE plastic is very suitable for use in production as its mechanical characteristics are similar to that of un-recycled HDPE plastic.